The Effectiveness of the Tamyiz Method in Improving Understanding of Arabic Vocabulary in Junior High Schools - Nurhaliza, Siti; Akbar, Doni Wahidul (Universitas Cokroaminoto Palopo, 2024)
Metode Tamyiz is a practical method to help translate Arabic vocabulary. The purpose of this study was to determine the effectiveness of the tamyiz method in improving the understanding of Arabic vocabulary at SMP Muhammadiyah 6, Jakarta. This study used a type of quantitative research with experimental design techniques (pre-experimental model, one-group pretest-posttest). The research was conducted in March 2024 at SMP Muhammadiyah 6, Jakarta. The population in this study was grade VIII students at SMP Muhammadiyah 6 Jakarta, totaling 30 people using saturated sample techniques. The data collection technique used in this study was pre- and post-test. And the technique to analyze the data uses normality tests, effectiveness tests, and paired sample t-tests with a significance level of 5%. The results of this study found that there was an increase in students' understanding of Arabic vocabulary using the tamyiz method. Therefore, it can be concluded that the tamyiz method is quite effective as a learning method that can significantly improve the understanding of Arabic vocabulary of grade VIII students at SMP Muhammadiyah 6 Jakarta.